2016
DOI: 10.1007/s12032-016-0832-y
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis: a possible foe to prostate cancer

Abstract: Prostate cancer (PCA) is the most common malignancy in men in USA, and the role of Trichomonas vaginalis (T. vag) in the development of PCA is still controversial. Clonogenic assay, PCNA staining, TUNEL staining and caspase-3 activity assay were used to investigate the in vitro role of T. vag in human prostate cancer. We further investigated the possible molecular mechanisms using RT-PCR and immunohistochemical staining. Culture supernatant of T. vag inhibits growth of PC-3 prostate cancer cells, and this corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…MIF produced from Tv has been reported to increase the proliferation of PCa cells, 22 while the culture medium of Tv has also been shown to be cytotoxic to PCa cells. 42 Our previous studies Moreover, many studies have suggested that chemokines, such as CCL2 (MCP-1) and CXC including CXCL8 are involved in the invasiveness and metastasis of PCa. 49,50 CCL2, a member of the CC(β) chemokine family, is thought to recruit monocytes to sites of inflammation and is reported to induce activation of CCR2 in PCa epithelial cells as well as breast cancer and multiple myeloma cells, thus stimulating their migration and proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…MIF produced from Tv has been reported to increase the proliferation of PCa cells, 22 while the culture medium of Tv has also been shown to be cytotoxic to PCa cells. 42 Our previous studies Moreover, many studies have suggested that chemokines, such as CCL2 (MCP-1) and CXC including CXCL8 are involved in the invasiveness and metastasis of PCa. 49,50 CCL2, a member of the CC(β) chemokine family, is thought to recruit monocytes to sites of inflammation and is reported to induce activation of CCR2 in PCa epithelial cells as well as breast cancer and multiple myeloma cells, thus stimulating their migration and proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 95%
“…The association between Tv infection and PCa still remains controversial. MIF produced from Tv has been reported to increase the proliferation of PCa cells, while the culture medium of Tv has also been shown to be cytotoxic to PCa cells . Our previous studies reported that prostate epithelial cells cultured with live Tv were induced cytotoxicity with inflammatory responses .…”
Section: Discussionmentioning
confidence: 97%
“…Following the 72 h incubation, the HCT-116 cells were detached, manually counted and analyzed using a clonogenic survival assay kit (BioVision, Inc., Milpitas, CA, USA), as previously described ( 12 , 13 , 18 20 ). The final HCT-116 cell survival results of the study were expressed as a percentage of the total colonies that were counted within the control group.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed method for PCNA staining has been previously described ( 12 , 13 , 18 20 ). To summarize, samples were incubated with 0.1% saponin (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) in 1% bovine serum albumin (Thermo Fisher Scientific, Inc.) and then incubated with polyclonal rabbit antibody for PCNA (sc-7907; dilution 1:100; Santa Cruz Biotechnology, Inc., Dallas, TX, USA) at room temperature for 1 h. The Avidin-Biotin Complex Immunoperoxidase system (Vector Laboratories, Inc., Burlingame, CA, USA) was used to amplify the immunoreactivity of the sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation